(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Cucumber (Cucumis sativus L.) is a popular vegetable worldwide, a ready-to-eat product, valuable for its special, refreshing taste and content of vitamins, minerals and antioxidants. In the logistics supply chain of cucumber fruits, the problem of storage under natural conditions is created, because after harvesting the fruits quickly lose freshness and deteriorate in quality within 2–3 days. Currently, there is a significant increase in the development of biodegradable edible packaging to ensure the safety and quality of fruits and vegetables after harvesting. One of the biopolymers for edible coatings of food products is gelatin, chitosan, pectin. Purpose of the work. The conducted studies aimed to determine the effect of treating cucumber fruits before storage with edible coatings based on high-molecular gelatin, agar-agar and chitosan on weight loss and to establish correlations between coating compositions. This will reduce product losses during storage and extend the duration of its consumption. The object of the study is the technology of pre-treatment of cucumber fruits using edible coatings based on gelatin, agar-agar and chitosan. The subject of the study is cucumber fruits, their weight loss and quality change during storage depending on the type of protective coating. Conclusions. Agar-agar-based coating provided the lowest weight loss of cucumber fruits – 3.1%, in uncoated fruits - 4.7%. Increasing the amount of agar-agar from 25 to 75% in the composition reduced weight loss from 3.2 to 3.4%. The difference between the minimum loss values ​​is statistically significant and is 1.65 at NIP05 = 0.79. The coefficient of variation is more than 25%, which confirms the significant difference between the options. The regression equation indicates the relationship between daily losses of cucumber fruits and natural mass losses, damage by microorganisms and physiological disorders. With increasing mass loss, daily losses increase by 0.059%, the increase in damage by microorganisms is 0.165%, physiological disorders are 0.093% A direct strong correlation (r = 0.9947) between the average level of daily mass losses and losses from damage by microorganisms is confirmed. Drageeing cucumber fruits affects the level of total mass losses of fruits by 72.1%.